Aesthetic-Based Learning Management Of Art And Culture(A Site Study at SMP Negeri 2 Purworejo) - Handayani, Tri, Prof. Dr. Budi Murtiyasa, M.Kom, Drs. HA. Dahlan Rais, M.Hum (2013)
The purposes of this study were to describe (1) the characteristics of teachers' teaching activity in the Aesthetic-Based Art and Culture Learning at SMP Negeri 2 Purworejo; (2) the characteristics of students' learning activity in the Aesthetic-Based Art and Culture Learning at SMP Negeri 2 Purworejo; and (3) the characteristics of interaction in the Aesthetic-Based Art and Culture Learning at SMP Negeri 2 Purworejo. It was a qualitative study with the main research subjects were the principal, teachers, and students. Methods used to collect data were interview, observation, and documentation. The analysis of data started from (1) data reduction, (2) data display, and (3) drawing conclusion. The validity of data was check used credibility, and transferability tests. The findings showed that (1) teachers were active in the aesthetic-based cultural art learning at SMP 2 Purworejo. This activeness could be seen from teachers' activities in preparing all instructional equipment such as musical instrument, drawing, coloring and dance CDs. Teachers packed learning with multi-method conducted in the form of individual and group learning. The concept of aesthetics was given together with the materials of art, music, theater, and dance through the instructional media. It is at once an aspect of assessment by teachers including the aspect of competence appreciation and recreation or creative arts and culture. (2) Students were active in the aestheticbased cultural art learning at SMP 2 Purworejo. This activeness was shown by doing practical activities both individual and group. Students exhibited art works of their creation that contained the appreciation and creative values like making table cloth patterned lurik batik with a combination of animals and plants pictures. Students in groups organized ensemble music with modern pop music arrangement. (3) The aesthetic-based art and culture learning at SMP 2 Purworejo ran interactively. There are one-way and two-way interactions. The one-way interaction existed when the teacher explained the difficult materials and students asked to give attention such as the material of tuning guitar with fingers. Two-way interaction pattern occurred when the students and teacher conducted a question and answer activity and also group practice. In making batik, teachers made groups and divided tasks to each member of the groups. Students prepared several equipments such as table cloth, wax, canting, chairs and so forth. While other students made batik with the mix of sido mukti, animal and plants patterns.